THE INFLUENCE OF PROFESSIONALISM AND INTEGRITY ON THE PERFORMANCE OF WEST PASAMAN TRAFFIC UNIT MEMBERS - Endang Tirtana Putra; Yurasti, Yurasti; Citra Suci Mantauv; Roza Gustika (Journal of Social and Economics Research, 2024)
This research aims to determine the influence of professionalism and integrity on the performance of West Pasaman traffic unit members. The sample for this research was 37 members of the traffic unit. The analysis technique in this research uses validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and R test2. The method used is associative research. The research results show that the professionalism variable partially has a positive and significant influence on performance as proven by the results of the t test where the significance value is 0.015 and the integrity variable partially has a positive and significant influence on performance with a significance value of 0.000. The coefficient of determination (R²) value obtained was 0.812. And the F test value was 173.500, which means that professionalism and integrity simultaneously have a significant effect on performance with a significance value of 0.000, which is less than 0.05.